English for business studies : a course for business studies and economics students : student's book - Mackenzie, Ian. (Cambridge : Cambridge University Press, 1997)
The three sectors of the economy. Management. Company structure. Work and motivation. Management and cultural diversity. Recruitment. Labour relations. Production. Products.
Keywords: English language; Business English; Foreign speakers; English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; English language -- Business English; English language -- Foreign countries